Análise multidimensional do processo integracionista do Mercado Comum do Sul - Bechlin, André Ricardo (2010)
This research is mainly aimed to assess from a multidimensional perspective that considers varying political, social, economic and technological integration of the stages of the Southern Common Market (MERCOSUR) in 1998 and 2008. The theoretical framework includes topics of the theory of regional economic integration; historical process of economic integration in Latin America; history of the formation process of MERCOSUR and its current situation. The methodology used was the Global Dimension of Regional Integration Model considering a total of 90 variables with 18 political, 16 social, 46 economic and technological 10. For each of the States Parties and Associates were calculated Global Regional Development Index and Regional Global Development, and through them we obtained the value for the Regional Integration Stage Index to the MERCOSUR, which is equal to 0.57037 in 1998 and 0.62222 in 2008, framing it as an integration process in development. Analyzing the indexes for each of the States Parties and Associates notes to uneven development between 1998 and 2008 Brazil showed a more than proportional growth in relation to other countries in all areas surveyed. The conclusion is that although the bloc's integration has improved, the effects obtained were not distributed equally among the countries given their heterogeneity.